Strategies in Ballistics Reconstruction in Shooting Deaths: Checklist, Methods, Tricks, and Pitfalls (Global Journal of Medical Research, 2024)
Background: The multidisciplinary type of Forensic Ballistics science is an essential database for the medical examiner to define the most compatible sequence of events and to motivate reconstructive hypotheses. In gunshot victims, analysis of biological data alone may be insufficient for recon-structive purposes. Knowledge of the basic general principles relating to mechanisms, indicators, operating systems, power supplies, types of bullets, and so on, can make the difference between a "sterile" autopsy and one that can be useful to judicial investigations. Results: The reconstruction of the event, the final phase of criminal investigation, must include the interpretation and re-composition of the various elements of evidence and the overall evaluation of the same to obtain a legal characterization.
Keywords: firearm; ballistic; medical examiner; forensic science